Cattle Settlement Policy and Nigeria’s troubled Federation: Ethno-religious Politics through other means - Omitola, Bolaji; Akinrinde, Olawale Olufemi; Omodunbi, Olumide Olumuyiwa; Adegboye, Damola Ibukun; Adedire, Solomon (Law Research Review Quarterly, 2021)
This article argues that the policy of the federal government of Nigeria in establishing settlement for herders who are mostly Fulani in different states of the country is perceived by other ethnic groups as advancement of ethnic and religious politics. This perception has led to counter ethno-religious narratives with accompanying increased tensions for the country. Ethno-religious politics has not only become the defining character of Nigerian federation overtime but its continuous unbridled expression, manifestation and dire consequences are currently threatening the existence of the country as a sovereign polity. This article through qualitative secondary data from media reports, scholarly articles, government publications and internet resources examines the Cattle Settlement policy, its merits and demerits within the context of a troubled federation. The article concludes on ways of resolving the emerging crisis through proper framing of the policy for wide acceptability taking into cognizance the diversity that defines the country’s existence and the need to pursue enduring peace in the polity.